2019
DOI: 10.1093/emph/eoz022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative psychopharmacology of autism and psychotic-affective disorders suggests new targets for treatment

Abstract: The first treatments showing effectiveness for some psychiatric disorders, such as lithium for bipolar disorder and chlorpromazine for schizophrenia, were discovered by accident. Currently, psychiatric drug design is seen as a scientific enterprise, limited though it remains by the complexity of brain development and function. Relatively few novel and effective drugs have, however, been developed for many years. The purpose of this article is to demonstrate how evolutionary biology can provide a useful framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 285 publications
0
4
1
2
Order By: Relevance
“…In fact, dysfunctional ionotropic NMDA receptors have been recently linked to multiple forms of ASD and emerging evidence showed that d-aspartate and d-serine are important neuromodulators of glutamatergic transmission [ 19 ]. These data suggest that targeting the NMDA receptor could have promising therapeutic potential in ASDs and experimental studies have been conducted with this aim [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, dysfunctional ionotropic NMDA receptors have been recently linked to multiple forms of ASD and emerging evidence showed that d-aspartate and d-serine are important neuromodulators of glutamatergic transmission [ 19 ]. These data suggest that targeting the NMDA receptor could have promising therapeutic potential in ASDs and experimental studies have been conducted with this aim [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…“The emerging, remarkable confluence of data from humans and animals suggests an opportunity for developing a rational pharmacology by targeting cortical KP metabolism for cognition enhancement in schizophrenia and beyond ” (Wonodi & Schwarcz, 2010). KYNA is the next frontier for neuropsychiatric diseases; the KP was described as a finger in every pie recently (Crespie, 2019; Savitz, 2020). KYNA‐centric pathophysiology (Koola, 2020) may be of considerable value in the treatment of many neuropsychiatric diseases.…”
Section: Schizophrenia and Beyondmentioning
confidence: 99%
“…Second, according to the diametric model of social brain disorders ( Crespi and Badcock, 2008 ; Crespi and Go, 2015 ; Crespi, 2016 , 2019 , 2020 ), autism and psychosis can be conceptualized as polar ends of a continuum of social cognition development, with normality at its center. Thus, autism is characterized by low mentalistic thought (i.e., social cognition) and high mechanistic thought (i.e., non-social cognition), and psychotic-affective conditions, such as schizotypy, are characterized by high mentalistic and low mechanistic thought ( Crespi and Badcock, 2008 ).…”
Section: Introductionmentioning
confidence: 99%